A systematic review of students’ awareness on cyberbullying at high school level of education - Raja Hassan, Raja Muhammad Faiz; Rahmatullah, Bahbibi; Saad, Aslina; Tareq, Ziadoon (Universitas Mercu Buana Yogyakarta, 2022)
Today's cyber world is becoming more accessible to anyone. Lack of education and awareness related to cyber security including bullying has contributed to the misuse of available facilities, especially social media. Cyberbullying is a serious concern among secondary students, and owing to the pandemic COVID-19, the majority of secondary students are required to attend class online in order to complete their studies. However, the use of technology in secondary school has a detrimental influence, as seen by the rise in cyberbullying instances among secondary pupils. Using the Scopus database, we discovered 36 publications connected to the term that was used. Following the screening, a total of 17 academic documents that are entirely connected to the study issue were obtained and examined. Thematic analysis performed shows several important aspects studied which looks at the impact, prevention, and knowledge of cyberbullying among secondary students, teachers, and parents. The findings also point towards raising awareness about the impact of cyberbullying on secondary students and how to prevent it. The goal of this systematic literature review is to raise awareness regarding cyberbullying's impact on high school or secondary level students.